Learning to learn: a critical realist exploration into the home established learning practices of a marginalised community in Port Elizabeth - Armstrong, Meredith (Rhodes University, Faculty of Education, Centre for Higher Education Research, Teaching and Learning, 2019)
This study was completed as part of a project exploring social inclusion and exclusion in South African higher education. In a globalised world, the achievement of a qualification from an institution of higher education is increasingly key to finding any sort of employment. This is particularly the case in South Africa where employment amongst black citizens is inordinately high. The aim of the research reported upon in this thesis was to better understand the construct of 'epistemological access' (Morrow, 1992), often used in relation to the needs of black working class students entering higher education, in relation to performance data (see for example, CHE, 2016) that repeatedly shows that black students fare less well than their white peers. Following what might be termed a 'social' approach to understanding access, this study begins long before most students have even heard of higher education and focuses on identifying the mechanisms that come into play at much earlier level of learning and literacy development. The study outlines the development of 'ways of being', or social practices, surrounding learning in a marginalised community in Port Elizabeth, in the Eastern Cape, South Africa. This was achieved by means of critical ethnography and it is therefore qualitatively based. The study shows how social structures enable or constrain a child's school readiness and how they then go on to support or impede progress in school where the language and literacy needed for educational success are further developed. The study therefore aims to allow us to explain global data indicating that the single greatest indicator of a young person's ability to access and succeed in higher education is the level of education of caregivers in their homes of origin. Examined from a critical perspective (i.e. with a concern for social justice), this study has made use of a framework using social, psychological and linguistic theory and more, particularly, the work of sociologist Margaret Archer (1995, 1996, 2003). The study makes particular use of Archer's 'morphogenetic framework' which allows for an analysis of the way structure and culture impact on a child's development over time. As I was concerned that my own social status might impact on the understandings I developed as a critical ethnographer, the study acknowledges my own experiences of learning and the way my own family sought to enhance them as enabling. In doing this, the study aims to better contribute to understandings of social justice in South Africa.
Keywords: Minorities -- Education (Higher) -- South Africa; Readiness for school -- Social aspects -- South Africa; Inclusive education -- Social aspects -- South Africa; Marginality, Social -- South Africa; Critical realism